2008
DOI: 10.1007/s00198-008-0725-9
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic markers of bone quality in alendronate-treated postmenopausal women

Abstract: Summary-Comparison of infrared spectroscopic images of sections from biopsies of placebotreated post-menopausal women and women treated for 3 years with 10 mg/day alendronate demonstrated significant increases in cortical bone mineral content, no alterations in other spectroscopic markers of "bone quality," but a decrease in tissue heterogeneity.Methods-The material properties of thick sections from iliac crest biopsies of seven alendronatetreated women were compared to those from ten comparably aged postmenop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
90
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 39 publications
11
90
2
Order By: Relevance
“…Without a complex statistical analysis requiring larger numbers, we can only suggest that no treatment corrected any FTIR-determined material property parameters in oim/oim of either sex to WT values. The increased heterogeneity discussed may be beneficial, because increased heterogeneity has been correlated with reduced fracture risk in untreated osteoporotic humans [6,14,20]. The lack of change in collagen maturity, noted to be slightly elevated in untreated male and female oim/oim cortical and cancellous bone, merits comment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without a complex statistical analysis requiring larger numbers, we can only suggest that no treatment corrected any FTIR-determined material property parameters in oim/oim of either sex to WT values. The increased heterogeneity discussed may be beneficial, because increased heterogeneity has been correlated with reduced fracture risk in untreated osteoporotic humans [6,14,20]. The lack of change in collagen maturity, noted to be slightly elevated in untreated male and female oim/oim cortical and cancellous bone, merits comment.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution (heterogeneity) of each parameter is calculated based on the full width at half maximum of the pixel histogram for spatial distribution in each individual image. Heterogeneity in adult human bone has been shown to decrease with bisphosphonate treatment [6,14,20]. These compositional parameters, taken together, provide an index of bone quality.…”
Section: Introductionmentioning
confidence: 99%
“…Using Fourier-transformed infrared spectroscopy (FTIR), Durchschlag and colleagues (30) showed that BP treatment prevented the maturation of collagen found in patients not treated with BPs and reduced collagen maturity in newly formed bone. Boskey and colleagues (31) reported no change in collagen maturity in women treated with alendronate. Donnelly and colleagues (32) showed similar mean values but a narrowed distribution of collagen maturity and enzymatic crosslinks in a small number of women with common proximal femoral fractures without features of atypia who had been treated with BPs for an average of 7 years.…”
Section: Insights Into the Pathogenesis Of Atypical Femoral Fracturesmentioning
confidence: 96%
“…(10,(58)(59)(60) Both short-term and long-term RIS administration resulted in mineral crystallites of decreased maturity/crystallinity compared to ALN, in general agreement with previously published reports showing that although RIS administration in postmenopausal women lowered this bone quality index compared to placebo, ALN did not. (12,13) Collagen cross-links are also important contributors to bone strength. (10,11,37,38) It should be noted that in cases for which bone strength and BMD exhibit divergent trends, the mineral maturity/crystallinity and collagen cross-links ratio correlate with the former rather than the latter.…”
Section: Discussionmentioning
confidence: 99%
“…(11) Spectroscopic analysis of biopsies from postmenopausal women who received either placebo or ALN (10 mg/d) for 3 years revealed no significant changes between the two groups in spectroscopic markers of bone quality (mineral/matrix ratio, crystallinity, carbonate/amide I ratio, and collagen maturity), except for a significant increase in cortical bone mineral content in the patients who were receiving ALN. (12) On the other hand, spectroscopic analysis of biopsies from postmenopausal women who received either placebo or RIS for 3 or 5 years showed that RIS arrested the tissue aging encountered in untreated osteoporosis. In particular, patients who received placebo exhibited increased mineral maturity/ crystallinity and collagen cross-link ratio after 3 and 5 years compared with baseline values, whereas patients who received RIS had no significant changes in either parameter at 3 or 5 years compared to baseline.…”
Section: Introductionmentioning
confidence: 99%